The Effect of Combined Method Training Circuit Training Plyometric on Power and Strength - Utomo, Ardyansyah Arief Budi; Nurhasan, Nurhasan; Wiriawan, Oce; Muhammad, Heryanto Nur (International Journal of Emerging Research and Review, 2024)
Objectives: The circuit training plyometric and 2 variable bound (power and strength) methods have not been combined much in research. This research tries to combine them to improve the quality of professional futsal athletes. Method: This research design uses research design matching only design. This type of research uses quasi experiments. The population in this research are professional futsal athletes in Madiun City, numbering 100 people. Meanwhile, the sample used is totalling 30 people. This research is limited only to manifold samples_sex the man who has an age between 18 and 20 years. Samples are divided into 2 groups, namely group experiment plyometric and group circuit training control. The variables of this research consist of from 1 variable free (circuit training plyometric) and 2 variables bound (power and strength). The instrument test in this research used a vertical jump test and leg dynamometer. Data collection techniques were carried out first in a way carry out normality tests and homogeneity tests. Data analysis techniques were carried out using formula mean, standard deviation, variance, percentage increase, paired sample t-test, one-way test anova, and post hoc comparison. Results: There is a difference in power before and after giving combined method training circuit training plyometric. So you can conclude that This combined method of circuit training plyometric is a method of proper exercise_ used to improve ability motor power. Then, for variable strength, it concluded that There is a difference in strength before and after giving combined method training circuit training plyometric. So you can conclude that This combined method of circuit training plyometric is a method of proper exercise to improve ability motor strength. Novelty: The novelty in this research is combining the circuit training plyometric and 2 variable bounds (power and strength).